Missense variants in the chromatin remodeler CHD1 are associated with neurodevelopmental disability. Issue 8 (2nd September 2017) - Pilarowski, Genay O; Vernon, Hilary J; Applegate, Carolyn D; Boukas, Leandros; Cho, Megan T; Gurnett, Christina A; Benke, Paul J; Beaver, Erin; Heeley, Jennifer M; Medne, Livija; Krantz, Ian D; Azage, Meron; et al.
Abstract : Background: The list of Mendelian disorders of the epigenetic machinery has expanded rapidly during the last 5 years. A few missense variants in the chromatin remodeler CHD1 have been found in several large-scale sequencing efforts focused on uncovering the genetic aetiology of autism. Objectives: To explore whether variants in CHD1 are associated with a human phenotype. Methods: We used GeneMatcher to identify other physicians caring for patients with variants in CHD1 . We also explored the epigenetic consequences of one of these variants in cultured fibroblasts. Results: Here we describe six CHD1 heterozygous missense variants in a cohort of patients with autism, speech apraxia, developmental delay and facial dysmorphic features. Importantly, three of these variants occurred de novo. We also report on a subject with a de novo deletion covering a large fraction of the CHD1 gene without any obvious neurological phenotype. Finally, we demonstrate increased levels of the closed chromatin modification H3K27me3 in fibroblasts from a subject carrying a de novo variant in CHD1 . Conclusions: Our results suggest that variants in CHD1 can lead to diverse phenotypic outcomes; however, the neurodevelopmental phenotype appears to be limited to patients with missense variants, which is compatible with a dominant negative mechanism of disease.